Photoswitchable stable charge-distributed states in a new cobalt complex exhibiting photo-induced valence tautomerism - Slota, M; Blankenhorn, M; Heintze, E; Vu, M; Hübner, R; Bogani, L (Royal Society of Chemistry, 2015)
We report the synthesis and magnetic and photomagnetic behaviour of a novel valence tautomeric cobalt complex, [Co(3,5-dbbq)2(μ-bpym)] (1) (3,5-dbbq = 3,5-di-tert-butyl-1,2-benzoquinone and μ-bpym = 2,2'-bipyrimidine). The synthesis is performed by reacting Co2(CO)8 and μ-bpym in the presence of the ligand 3,5-dbbq in a mixed solvent under inert atmosphere. The magnetic behavior clearly shows the presence of electron transfer from the catecholate ligand to the cobalt center, producing valence tautomers of [Co(II)(SQ)2] with a transition temperature (T1/2) of 215 K. Photomagnetic studies, performed via both SQUID magnetometry and X-band electron paramagnetic resonance, show the clear presence of photoinduced valence tautomerism, at temperatures considerably higher than previous systems. A metastable charge distribution is observed, strengthening previous investigations on the character of mixed valence ligands. Entropy-driven valence tautomeric interconversion is observed, and drives the transition to the most stable charge distribution. The complex has the ability to coordinate and can be used as a photoswitchable building block, with the photomagnetic characterisation evidencing a metastable state lifetime of the photo-induced valence tautomeric process of ca. 2.9 × 10(4) s below 20 K. The observed yields are higher than ones in similar systems, showing that tiny changes in the molecular structures may have a huge impact.